#TITLE_ALTERNATIVE# - HASAN DAMI LATALLENGKANG (NIM 13203184), SYAFRULLAH
Anti Air Cannon is one kind of weapons which is have a control system applicated for directing the firing bolt to the target on the sky. On the mini-scale model of anti air cannon, that have been built from Puma's manipulator robot, DC servo motor is used as an actuator for moving to the desired position. One kind of servo motor that using on Puma's manipulator robot is Tamagawa TN 3053N. Controlling on position and velocity of servo motor are handled by adding proportional, integral and derivatif controllers. For defining the coefficients of PID controllers, an experimental approach is used using Ziegler-Nichols's Tuning Method. An examining is done by observing the response of servo motor, then analysed, until the system of servo motor have a good stability point.